2021
DOI: 10.1177/00220345211022273
|View full text |Cite
|
Sign up to set email alerts
|

Saliva and Serum Protein Adsorption on Chemically Modified Silica Surfaces

Abstract: Biomaterials, once inserted in the oral cavity, become immediately covered by a layer of adsorbed proteins that consists mostly of salivary proteins but also of plasma proteins if the biomaterial is placed close to the gingival margin or if it becomes implanted into tissue and bone. It is often this protein layer, rather than the pristine biomaterial surface, that is subsequently encountered by colonizing bacteria or attaching tissue cells. Thus, to study this important initial protein adsorption from human sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…From the moment dental implants are inserted in the oral cavity, the fate of maintaining their physicochemical properties, especially the integrity of the protective TiO 2 passive layer against corrosion, is highly dependent on the challenging conditions of the hostile electrolytic oral environment [ 8 ]. Usually, the oral fluids (i.e., saliva, blood plasma) are characterized by the presence of organic and inorganic substances in combination with a pH buffering mechanism that regulates the hypotonic and physiological condition of the medium (pH between 6 and 7) [ 15 , 16 ]; however, some factors such as microbial metabolites and corrosive substances can reduce the pH, turning the environment acidic and highly reactive to chemically attack the metallic surfaces [ 7 , 17 , 18 ].…”
Section: Dental Implants Meet the Challenges Of The Reactive Oral Environmentmentioning
confidence: 99%
“…From the moment dental implants are inserted in the oral cavity, the fate of maintaining their physicochemical properties, especially the integrity of the protective TiO 2 passive layer against corrosion, is highly dependent on the challenging conditions of the hostile electrolytic oral environment [ 8 ]. Usually, the oral fluids (i.e., saliva, blood plasma) are characterized by the presence of organic and inorganic substances in combination with a pH buffering mechanism that regulates the hypotonic and physiological condition of the medium (pH between 6 and 7) [ 15 , 16 ]; however, some factors such as microbial metabolites and corrosive substances can reduce the pH, turning the environment acidic and highly reactive to chemically attack the metallic surfaces [ 7 , 17 , 18 ].…”
Section: Dental Implants Meet the Challenges Of The Reactive Oral Environmentmentioning
confidence: 99%
“…This applies to solutions that contain hundreds of different proteins, such as human serum and saliva used in our study. 48 Lehnfeld et al 49 showed that maximum protein adsorption on chemically modified silica surfaces occurred after one hour for saliva and 10 min for the much higher concentrated human serum. However, they observed that adsorbed proteins did not correlate linearly with surface physicochemical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…We used three mixed proteins due to their availability and cost performance. The approximate molecular weights of BMP, BSA, and collagen type I are 26, 66, and 300 kDa, respectively [58]. The size of the protein is a key element for apatite binding.…”
Section: Discussionmentioning
confidence: 99%